A Novel Constraint Method During Solution Treatment to Suppress Heating Rate‐Dependent Martensitic Stabilization in Cu–17.0Al–10.5Mn Alloy. Issue 7 (8th March 2018) - Yang, Qin; Chen, Jie; Meng, Yutang; Ge, Jiqiang; Wang, Shanling; Peng, Huabei; Wen, Yuhua
Abstract : Martensitic stabilization in copper‐based shape memory alloys can be suppressed by up‐quenching treatment through lowering vacancy concentration. Nevertheless, the up‐quenching time should be continuously extended to suppress martensitic stabilization as the recovery heating rate lowered. In terms of cost, it is not advisable to extend the up‐quenching time infinitely to suppress the heating rate‐dependent martensitic stabilization. In this paper, instead of eliminating vacancies through up‐quenching treatment, we focus on reducing vacancies from their origin, that is, the process of solution treatment. We investigate differences in the vacancy concentration and the resulting heating rate‐dependent martensitic stabilization in Cu–17.0Al–10.5Mn (at%) alloys subjected to solution treatment with and without constraint. The results show that the vacancy concentration in the unconstrained samples is remarkably lower than that in the constrained ones, leading to the suppression of heating rate‐dependent martensitic stabilization. We propose a novel constraint method during solution treatment avoiding shape change and suppressing martensitic stabilization simultaneously. Abstract : We found that the vacancy concentration in the samples of Cu–17.0Al–10.5Mn (at%) alloys subjected to solution treatment without constraint was remarkably lower than that in the constrained ones, leading to the suppression of heating rate‐dependent martensitic stabilization. We proposed a novel constraint method during solution treatment avoiding shape change and suppressing heating rate‐dependent martensitic stabilization simultaneously.